2006
DOI: 10.1021/es051667u
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Activity of Polychlorinated Biphenyls Present in Human Tissue and the Environment

Abstract: This study evaluated the estrogenicity of polychlorinated biphenyls (PCBs) present in environmental media and human tissue and assessed exposure pathways for PCB-derived estrogenic potency in air, soil, and dust from New Bedford, MA, an area with a PCB-contaminated Superfund site. Thirty-four PCB congeners were assayed for estrogenic potency using E-SCREEN, an assay based on the estrogen-dependent proliferation of MCF-7 cells in vitro. Childhood exposure to estradiol-equivalents via PCBs in environmental media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 45 publications
1
65
3
Order By: Relevance
“…Considerable interest has focused on the possible health effects of PCBs, a class of OC compounds used widely in the manufacturing of electrical equipment and other industrial applications until the institution of bans in the 1970s (banned in Norway in 1980). Experimental evidence suggests that some PCBs may exert estrogenic and possibly antiandrogenic effects and induce cytochrome p450 activity (Bonefeld-Jorgensen et al 2001;DeCastro et al 2006;Portigal et al 2002;Soto et al 1995;Wolff et al 1997). In our study, we did not observe a clear association between PCB levels and TGCT risk.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Considerable interest has focused on the possible health effects of PCBs, a class of OC compounds used widely in the manufacturing of electrical equipment and other industrial applications until the institution of bans in the 1970s (banned in Norway in 1980). Experimental evidence suggests that some PCBs may exert estrogenic and possibly antiandrogenic effects and induce cytochrome p450 activity (Bonefeld-Jorgensen et al 2001;DeCastro et al 2006;Portigal et al 2002;Soto et al 1995;Wolff et al 1997). In our study, we did not observe a clear association between PCB levels and TGCT risk.…”
Section: Discussioncontrasting
confidence: 92%
“…(BonefeldJorgensen et al 2001;DeCastro et al 2006;Wolff et al 1997). The only other published findings regarding PCBs and TGCTs come from the Swedish case-control study (Hardell et al 2003(Hardell et al , 2004; in that study, no difference in PCB levels between cases and controls was observed.…”
Section: Discussionmentioning
confidence: 97%
“…The non-dioxin-like PCBs weakly interact with estrogen and thyroid receptors and with transport proteins, and the hydroxylated metabolites of PCBs may be more potent mediators of these actions (Azulmozhiraja et al, 2005;DeCastro et al, 2006;Langer et al, 2005;Purkey et al, 2004;Kitamura etal., 2005;You et al, 2006). Variations in thyroid hormone levels have been associated with PCB exposures in human populations (Langer et al, 2007a;Meeker et al, 2007;Otake et al, 2007;Wang et al, 2005).…”
Section: Geometric Selected Percentilesmentioning
confidence: 99%
“…PCBs are now ubiquitous in environmental media, buildings, wildlife, food, and humans [19]. Several PCB congeners have been found to be oestrogenic in studies of congeners that are historically present in human tissue and the environment [20,21].…”
Section: Application To Data For Weakly Oestrogenic Pcbmentioning
confidence: 99%